(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Article peer reviewed. An article based on the same research is due to be published in Proceedings of the Conference “Gli elementi essenziali delle religioni nella giurisprudenza delle Corti” held in Rome at the LUISS “Guido Carli”, May 12, 2015. SUMMARY: 1. Introduction – 2. Understanding the complexity: the role of religions in the Indian, Pakistani and Malaysian contexts – 3. The discipline of the religious phenomenon in India: which influences from foreign models in the Constitution? – 4. The Supreme Court and the “essential elements of religion” doctrine – 5.The migration of the Indian essential practice doctrine in Pakistan and Malaysia – 5.1 Interpreting the essential practice doctrine in Pakistan: the long-lasting history of the Ahmadis (non)recognition – 5.2 Cloths and Words always matter. The essential doctrine in Malaysia – 6. Concluding Remarks Abstract: The Supreme Court of India elaborated the “essential elements doctrine” to ascertain which elements are fundamental for a religious practice and which may be purged, as mere superstition, by the intervention of the State without infringing the principle of State neutrality in religious affairs. The doctrine has been discussed and in some cases applied also by constitutional interpreters in Pakistan and Malaysia, whose Constitutions echo the provisions on freedom of religion of the Union of India but also establish Islam as the religion of the State. Therefore, the present essay discusses the interpretation of constitutional provisions by the Supreme Court of India in order to introduce the essential elements doctrine as well as its application by the Pakistani and Malaysian Courts with the aim to asses, relying on the theory of cross-fertilization, whether they merely imported the doctrine or adapted it to the national contexts